PRODUKTIVITAS KERJA SEBAGAI HASIL DARI KEPEMIMPINAN KEPALA SEKOLAH DAN ETOS KERJA GURU DENGAN PRODUKTIVITAS KERJA GURU (Studi pada Guru di SD Swasta Se-Kecamatan Cileungsi Kabupaten Bogor) - Thamrin Abdullah (MAGMA : JURNAL MAGISTER MANAJEMEN, 2013)
This research is to study the correlation between principals leadership and teachers work ethic with teachers work productivity both individually and collectivelly. Among 93 teachers were surveyed and were selected as samples for the research. Normality, simple regression, multiple regression, homogeneity, simple correlation, multiple correlation, and partial correlation are several data analysis method that were used in this research. The result of this research imply that: Firstly, a positive and significant corelation was found between principals leadership with teachers work productivity and expressed in a form of regression equation as ? = ? = 100.073 + 0.249 X1. The correlation coefficient is ry1 = 0.246 and determination coefficient is r2y1 = 0.06. This means that principals leadership contributed as much as 6% towards teachers work productivity. Secondly, a positive and significant corelation was found between teachers work ethic with teachers work productivity and expressed in a form of regression equation as ? = 37.701 + 0.675 X2. The correlation coefficient is ry1 = 0.615 and determination coefficient is r2y2 = 0.378. This means that principals leadership contributed as much as 37.8% towards teachers work productivity. Thirdly, this research also found that there is a positive and significant corelation between principals leadership and teachers work ethic along with teachers work productivity which is expressed in regression form of ? = 8.613 + 0.232X1 + 0.667X2 and multiple correlation of Ry12 = 0.656 and determination coefficient is Ry12 = 0.43. This means both contribute 43% to the teachers work productivity. This research was also shows that the correlation strength between the principals leadership to the teachers work productivity is lower than the correlation strength between teachers work ethic to the teachers work productivity. Thus, the teachers work ethic are the main variable in this research and it contribute the biggest contribution to the teachers work productivity.Keywords: principals leadership, teachers work ethic, teachers work productivity